STUDI KRITIS ATAS HADIS TENTANG RUKYAT DAN HISAB - Fuad Fansuri (Rausyan Fikr: Jurnal Ilmu Studi Ushuluddin dan Filsafat, 2017)
The determination of the beginning and the end of Ramadan has a fundamental meaning for Muslims because it is associated with the implementation of fasting. In Indonesia, most of the year the issue becomes a polemic in society; it even tends to cause a conflict among Muslims. This paper focuses on the exposure of takhri> j hadith about rukyat and hisab on its practice on determining the beginning and the end of Ramadan in Indonesia.